2020
DOI: 10.1007/s12155-020-10108-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultrasound Pretreatment for Enhanced Anaerobic Digestion of Sida hermaphrodita

Abstract: The influence of ultrasonic pretreatment with specific energy input ranging from 25 to 550 kJ/kg volatile solids on the mixture of Sida hermaphrodita (L.) Rusby mixed with cattle manure disintegration and subsequent anaerobic digestion was assessed. The pretreatment process led to significant increase in the biomass solubility by 21.9% as chemical oxygen demand and enhanced biogas yield by 157% (567.1 L biogas/kg volatile solids) when the specific energy input was from 200 to 550 kJ/kg. However, only pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…After the application of ultrasounds, Dudek et al [143] recorded highest yields from the fermentation of S. hermaphrodita together with cattle manure, obtaining 1011 dm 3 kg −1 oDM with a methane content 66-69%. Kisielewska et al [149] also demonstrated the effectiveness of ultrasound in increasing solubilisation and biogas production from a mix of S. hermaphrodita and cattle manure, obtaining methane yields of up to 337.9 dm 3 kg −1 oDM. After applying hydrodynamic cavitation to a mix of S. hermaphrodita and cattle manure for 20 min, Zieliński et al [144] produced a maximum methane yield of 439.1 dm 3 kg −1 DM.…”
Section: Growing Sida Hermaphrodita and Silphium Perfoliatum As Solidmentioning
confidence: 99%
See 1 more Smart Citation
“…After the application of ultrasounds, Dudek et al [143] recorded highest yields from the fermentation of S. hermaphrodita together with cattle manure, obtaining 1011 dm 3 kg −1 oDM with a methane content 66-69%. Kisielewska et al [149] also demonstrated the effectiveness of ultrasound in increasing solubilisation and biogas production from a mix of S. hermaphrodita and cattle manure, obtaining methane yields of up to 337.9 dm 3 kg −1 oDM. After applying hydrodynamic cavitation to a mix of S. hermaphrodita and cattle manure for 20 min, Zieliński et al [144] produced a maximum methane yield of 439.1 dm 3 kg −1 DM.…”
Section: Growing Sida Hermaphrodita and Silphium Perfoliatum As Solidmentioning
confidence: 99%
“…The application of pre-treatments can increase methane yields, but they incur additional energy costs [138,148,150]. For example, Kisielewska et al [149] concluded that the increase in biogas and methane yields after ultrasound pre-treatments could not be justified from an energy balance perspective. Szwaja et al [118] estimated that 56 GJ ha −1 y −1 of electricity could be produced from S. hermaphrodita through a Rankine cycle (35% efficiency).…”
Section: Energy Balances and Lcasmentioning
confidence: 99%
“…The amounts of soluble COD and TOC were 771 ± 83 mgO 2 /L (solubilization degree 72.4 ± 7.3%) and 560 ± 42 mg/L (solubilization degree 77.5 ± 8.5%), respectively (Table 4). Ultrasonication is a very popular and effective mechanical pretreatment method used for treating different kinds of biomass prior to AD [44][45][46][47][48]. This method improves the biodegradability of biomass by disrupting its structure, thus changing its physical, chemical, and biological properties [45,49].…”
Section: Effects Of Ultrasonic Pretreatment On Solubilization Of Orga...mentioning
confidence: 99%
“…Ultrasound is sound waves with frequencies above 20 kHz, and has promising effect on cell wall disruption and accessible surface area changes. A recent study has suggested that ultrasound pretreatment led to significant improvement in lignocellulosic biomass solubility and biofuel yield ( Marta et al, 2020 ). However, irradiation pretreatment, when used alone, has different defects, such as the formation of inhibitors and high energy consumption, and is now often combined with other pretreatment options.…”
Section: Current Technologies For the Pretreatment Of Lignocellulosicmentioning
confidence: 99%